Correlation between Renal Histopathology and Differential Renal Function in Unilateral Congenital Ureteropelvic Junction Obstruction in Children (The Planet, 2021)
Congenital ureteropelvic junction (UPJ) obstruction is the commonest cause of paediatric hydronephrosis. This study was done to define the relationship of renal histopathological changes with differential renal function (DRF) and outcome of pyeloplasty in a group of patients undergoing primary pyeloplasty for UPJ obstruction. A total of 16 consecutive patients with unilateral UPJ obstruction underwent renal biopsy at the time of pyeloplasty. Patient’s age ranges from 30 days to 11 years with a mean (+SD) of 4.94+4.27 years. Renal histopathological changes were graded into three groups according to the severity. In this study 43.75% patients were in Grade-I, 43.75% in Grade-II and 12.5% patients were in Grade-III. Histopathological findings were abnormal in 56.25% patients and normal in 43.75% patients. Most of the kidneys showed post-operative improvement of DRF except one, on follow-up renal scan after 6 months. In patients of grade-I complete functional recovery was observed post-operatively after six months. In the other two grades functional recovery was more in terms of percent change but complete functional recovery in such patients was not seen. Dysplastic kidneys also showed improvement in post-operative renal function, that indicates the efficiency of pyeloplasty in an obstructed kidney. Patients of unilateral UPJ obstruction with a pre-operative DRF less than 35% have a high probability of severe histopathological changes and a low probability of full functional recovery. This study shows that histopathologically normal kidneys have a higher DRF than dysplastic (abnormal) kidneys and complete recovery of renal function is expected in these patients after pyeloplasty. In conclusion, differential renal function on diuretic renography correlated positively with histopathological grading. Pyeloplasty improves general wellbeing and growth of the children.
Keywords: Congenital ureteropelvic junction obstruction; pyeloplasty; differential renal function